BRESSE-TIMOSHENKO SYSTEM : WELL-POSSEDNESS AND STABILITY RESULTS - YAZID, F.; OUCHENANE, D. (University of Eloued جامعة الوادي, 2019)
In this paper, we consider a Bresse-Timoshenko type system with distributed delay term. Under suitable assumptions, we establish the global well-posedness of the initial and boundary value problem by using the Faedo- Galerkin approximations and some energy estimates. By using the energy method, we show the exponential stability results for the system with delay in vertical displacement.
Working paper.3rd International Conference in Operator Theory, PDE and Applications. April 23-24- 2019. Faculty of Exact Science. Mathematics Department. University of ElOued